2001
DOI: 10.1128/jvi.75.24.12047-12057.2001
|View full text |Cite
|
Sign up to set email alerts
|

Sequences in the 5′ Nontranslated Region of Hepatitis C Virus Required for RNA Replication

Abstract: Sequences in the 5 and 3 termini of plus-strand RNA viruses harbor cis-acting elements important for efficient translation and replication. In case of the hepatitis C virus (HCV), a plus-strand RNA virus of the family Flaviviridae, a 341-nucleotide-long nontranslated region (NTR) is located at the 5 end of the genome. This sequence contains an internal ribosome entry site (IRES) that is located downstream of an about 40-nucleotide-long sequence of unknown function. By using our recently developed HCV replicon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
239
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(250 citation statements)
references
References 53 publications
6
239
0
5
Order By: Relevance
“…RNAs were quantified by a real-time, 59 exonuclease PCR (TaqMan) assay using specific primer/probe sets. For HCV the set recognized a portion of the HCV 59 untranslated region (nt 130-290) required for efficient RNA replication (Friebe et al, 2001): HCVfor, 59-CGGGAGAGC-CATAGTGG-39; HCVrev, 59-AGTACCACAAGGCCTTTCG-39; HCVprobe, 59-6-FAM-CTGCGGAACCGGTGAGTACAC-TAMRA-39. This primer/probe set was originally described and characterized by Takeuchi et al (1999), and enables detection of as few as 10 copies of HCV RNA.…”
Section: Methodsmentioning
confidence: 99%
“…RNAs were quantified by a real-time, 59 exonuclease PCR (TaqMan) assay using specific primer/probe sets. For HCV the set recognized a portion of the HCV 59 untranslated region (nt 130-290) required for efficient RNA replication (Friebe et al, 2001): HCVfor, 59-CGGGAGAGC-CATAGTGG-39; HCVrev, 59-AGTACCACAAGGCCTTTCG-39; HCVprobe, 59-6-FAM-CTGCGGAACCGGTGAGTACAC-TAMRA-39. This primer/probe set was originally described and characterized by Takeuchi et al (1999), and enables detection of as few as 10 copies of HCV RNA.…”
Section: Methodsmentioning
confidence: 99%
“…NC_009823) contains one stemloop structure (stem-loop I, SLI) (Honda et al, 1999), and two microRNA 122 (miR-122) binding sites (S1 and S2) (Henke et al, 2008;Jopling, 2008;Jopling et al, 2005;Machlin et al, 2011). It has been shown that the SLI is important for viral RNA replication (Friebe et al, 2001;Luo et al, 2003), and we demonstrated that it is essential for the viability of infectious HCV genotype 1-6 recombinants (Li et al, 2011a). miR-122 is a liver-abundant miRNA (Chang et al, 2004), and it stimulates viral RNA replication and translation by directly binding to S1 and S2, as well as to upstream nucleotides, in the HCV 5¢UTR (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1b). The extreme 59 end of the genome including domain I is not part of the IRES but is essential for replication (Rijnbrand et al, 1995;Friebe et al, 2001). Nine cloned variants corresponded to the consensus sequence and make up the prevalent quasispecies.…”
Section: Quasispecies Distribution In the 5 § Ntrmentioning
confidence: 99%
“…Since the HCV IRES contains cis-acting elements for translation as well as replication (Friebe et al, 2001;Reusken et al, 2003), we tested the stem-loop IIIa variant in selectable HCV replicons, which enable the study of viral RNA replication in cell culture (Lohmann et al, 1999). In these replicons the region encoding the structural proteins is replaced by a neomycin phosphotransferase gene, which upon expression confers resistance to G418.…”
Section: Effect Of Stem-loop Iiia Mutations On Replicationmentioning
confidence: 99%
See 1 more Smart Citation